Perceived organisational support and well-being: The role of psychological capital as a mediator - Roemer A; Harris C (AOSIS, 2018)
Orientation: Today’s competitive work environment requires organisations and employees to successfully cope with challenges to maintain healthy levels of well-being. It is, therefore, imperative to investigate which organisational and psychological factors contribute to well-being in employees. Research purpose: This study served to analyse whether psychological capital (PsyCap) mediates the relationship between perceived organisational support (POS) and well-being. Motivation for the study: In light of the positive psychology movement, this study aimed to investigate how positive constructs actively contribute to employee well-being. Knowledge of organisational and psychological factors that enhance well-being in employees will be of great benefit to organisations that aim to create positivity in the workplace in order to avoid the negative consequences of work-related stress and a toxic work environment. Research approach/design and method: A cross-sectional, non-experimental design, applying convenience and snowball sampling, was used to recruit 159 South African employees who completed an online survey that assessed the constructs under investigation. Main findings: It was found that POS, PsyCap and well-being are positively correlated to one another. Moreover, hierarchical regression analyses revealed that PsyCap fully mediates the relationship between POS and well-being. Practical/managerial implications: These findings imply that organisations should be committed to target their employees’ PsyCap to enhance well-being in their workforce. Contribution/value-add: The findings show that it is not sufficient just to provide organisational support to enhance well-being. Organisations also need to acknowledge the important role of their employees’ PsyCap to ensure that they are well equipped to deal with challenges in the workplace while maintaining healthy levels of well-being.